VizieR Online Data Catalog: X-ray supernova remnants in LMC (Maggi+, 2016) - Maggi, P.; Haberl, F.; Kavanagh, P. J.; Sasaki, M.; Bozzetto, L. M.; Filipovic, M. D.; Vasilopoulos, G.; Pietsch, W.; Points, S. D.; Chu, Y. -H.; Dickel, J.; Ehle, M.; et al. (2016)
The processing of all available XMM-Newton data in the LMC region, and those of the VLP survey in particular, was done with the data reduction pipeline developed in our research group over several years. Various non-X-ray data were used to supplement the XMM-Newton observations. They allow us to assess e.g. the relation between the population of SNRs and large scale structure of the LMC, or to evaluate doubtful candidates in the sample compilation. We compiled a sample of 59 definite SNRs, cleaned of misclassified objects and doubtful candidates. (2 data files).
Keywords: Magellanic Clouds; Supernova Remnants; X-ray sources